Rare surfactant‐related variants in familial and sporadic pulmonary fibrosis. Issue 12 (2nd October 2022) - Sutton, Rachel M.; Bittar, Humberto Trejo; Sullivan, Daniel I.; Silva, Agustin Gil; Bahudhanapati, Harinath; Parikh, Anishka H.; Zhang, Yingze; Gibson, Kevin; McDyer, John F.; Kass, Daniel J.; Alder, Jonathan K.
Abstract: The role of constitutional genetic defects in idiopathic pulmonary fibrosis (IPF) is increasingly appreciated. Monogenic disorders associated with IPF affect two pathways: telomere maintenance, accounting for approximately 10% of all patients with IPF, and surfactant biology, responsible for 1%–3% of cases and often co‐occurring with lung cancer. We examined the prevalence of rare variants in five surfactant‐related genes, SFTPA1, SFPTA2, SFTPC, ABCA3, and NKX2‐1, that were previously linked to lung disease in whole genome sequencing data from 431 patients with IPF. We identified functionally deleterious rare variants in SFTPA2 with a prevalence of 1.3% in individuals with and without a family history of IPF. All individuals had no personal history of lung cancer, but substantial bronchiolar metaplasia was noted on lung explants and biopsies. Five patients had novel missense variants in NKX2‐1, but the contribution to disease is unclear. In general, patients were younger and had longer telomeres compared with the majority of patients with IPF suggesting that these features may be useful for identifying this subset of patients in the clinic. These data suggest that SFTPA2 variants may be more common in unselected IPF cohorts and may manifest in the absence of personal/family history of lung cancer or IPF.